2017
DOI: 10.1038/ncb3625
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukaemia disrupts endogenous myelo-erythropoiesis by compromising the adipocyte bone marrow niche

Abstract: Acute myeloid leukaemia (AML) is distinguished by the generation of dysfunctional leukaemic blasts, and patients characteristically suffer from fatal infections and anaemia due to insufficient normal myelo-erythropoiesis. Direct physical crowding of bone marrow (BM) by accumulating leukaemic cells does not fully account for this haematopoietic failure. Here, analyses from AML patients were applied to both in vitro co-culture platforms and in vivo xenograft modelling, revealing that human AML disease specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
167
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(178 citation statements)
references
References 64 publications
10
167
0
1
Order By: Relevance
“…A series of studies over the past decade has shown that the presence of AML blasts in bone marrow leads to functional alterations in stromal components with emergence of a leukemia-permissive niche [15,27,[48][49][50]. Recently, investigators have also begun to provide detailed analyses of residual hematopoietic cells in the AML-BM, revealing the initially surprising, and seemingly selective, quiescence and preservation of LT-HSC [16,18,22,23,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies over the past decade has shown that the presence of AML blasts in bone marrow leads to functional alterations in stromal components with emergence of a leukemia-permissive niche [15,27,[48][49][50]. Recently, investigators have also begun to provide detailed analyses of residual hematopoietic cells in the AML-BM, revealing the initially surprising, and seemingly selective, quiescence and preservation of LT-HSC [16,18,22,23,51].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the depletion of highly susceptible HSPC, HSC have proved to be more resilient during leukemic invasion, and multiple groups reported the relative accumulation of primitive hematopoietic cells in both murine models and xenograft studies [8,15,16,[21][22][23]. Unlike the depletion of highly susceptible HSPC, HSC have proved to be more resilient during leukemic invasion, and multiple groups reported the relative accumulation of primitive hematopoietic cells in both murine models and xenograft studies [8,15,16,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cBMA number is modestly depleted by a prostaglandin E 2 receptor type 4 agonist in ovariectomized rats 25 . Although not measured in rodents, it appears likely that both rBMAT and cBMAT are reduced in response to profound starvation 54 , blood-letting 55 , leukemia 34 , and infection 56 . Thus, whilst the term “constitutive” as a descriptor of some BMAT depots has merit, there are also caveats that diminish its dogmatic applicability.…”
Section: Development and Regulation Of Bmat In Humans And Rodentsmentioning
confidence: 96%
“…For instance, three weeks of cold exposure stimulates a dramatic and specific decrease in size and number of rBMAs in proximal tibia 21 . Other specific negative regulators of rBMA size or morphology include fasting 30 , intracerebral 31 or subcutaneous 32 leptin, intraperitoneal β 3 -agonist 33 , acute myeloid leukaemia 34 , exercise 35 and lactation 36 , some of which will be discussed in detail later within this review. Although development of rBMAT is independent of the lipodystrophy gene caveolin-1 ( Cav1 ), accumulation of rBMAs in proximal tibia is largely dependent on expression of another lipodystropy gene, cavin-1( Ptrf ) 21 .…”
Section: Development and Regulation Of Bmat In Humans And Rodentsmentioning
confidence: 99%
See 1 more Smart Citation